"Argumente Hin, Argumente Her." Regularity and Idiomaticity in German N Hin, N Her. Issue 3 (1st August 2017) - Finkbeiner, Rita
Abstract : This paper seeks to find the best linguistic analysis of the German semispecified, productive pattern N hin, N her (for example, Krieg hin, Krieg her, es muss eine gute Show werden 'War or no war, it must be a good show'). The basic question is whether the properties of N hin, N her can be accounted for in a rule-based approach or whether they are to be regarded as idiosyncratic properties of this construction. One of the characteristic features of N hin, N her is the identity of the nouns. This raises the question of whether or not N hin, N her is an instance of syntactic reduplication. It is shown that rule-based copying accounts fail when they are applied to the case of N hin, N her . The paper argues for an alternative, constructionist account of N hin, N her, which is able to cover both regular and idiosyncratic aspects of the construction in a systematic fashion. However, the paper goes beyond a standard constructionist account by also arguing that the idiosyncratic features of the construction can be further explained if one takes into account general pragmatic principles. This requires a theory that incorporates a systematic interface with pragmatics. *